The Risks of Incident and Recurrent Clostridium difficile-Associated Diarrhea in Chronic Kidney Disease and End-Stage Kidney Disease Patients: A Systematic Review and Meta-Analysis - Parkpoom Phatharacharukul (2018)
© 2015, Springer Science+Business Media New York. Background: The objective of this systematic review and meta-analysis was to assess the risks of incident and recurrent Clostridium difficile-associated diarrhea in patients with chronic kidney disease (CKD) and end-stage renal disease (ESRD) requiring dialysis. Methods: A literature search was performed from inception to February 2015. Studies that reported relative risks, odds ratios, or hazard ratios comparing the risks of C. difficile-associated diarrhea in patients with CKD or ESRD versus those without CKD or ESRD were included. Pooled risk ratios (RRs) and 95 % confidence intervals (CIs) were calculated using a random-effect, generic inverse variance method. Results: Twenty studies (nine case–control, seven cohort, and four cross-sectional studies with 162,218,041 patients) were included in the meta-analysis. Pooled RRs of C. difficile-associated diarrhea in patients with CKD and ESRD were 1.95 (95 % CI 1.81–2.10) and 2.63 (95 % CI 2.04–3.38), respectively. When meta-analysis was limited only to cohort and case–control studies with confounder-adjusted analysis, the pooled RRs of C. difficile-associated diarrhea in patients with CKD and ESRD were 1.89 (95 % CI 1.75–2.05) and 2.50 (95 % CI 1.49–4.17), respectively. The pooled RR of recurrent C. difficile-associated diarrhea in patients with CKD was 2.61 (95 % CI 1.53–4.44). Data on the risk of recurrent C. difficile-associated diarrhea were limited. Conclusion: This meta-analysis demonstrates significantly increased risks of incident and recurrent C. difficile-associated diarrhea in patients with CKD. Furthermore, the magnitude of increased risk of C. difficile-associated diarrhea in ESRD patients is even higher.